Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ijms19123797
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Marker of Inflammation: Azurocidin in Patients with ST Segment Elevation Myocardial Infarction

Abstract: (1) To investigate the role of azurocidin, an antimicrobial protein, in patients with ST segment elevation myocardial infarction (STEMI). (2) This single-center prospective observational study included patients with STEMI and healthy age- and sex-matched control subjects. Baseline demographic, clinical and biochemical data were compared between the two groups. Azurocidin levels at baseline were determined using an enzyme-linked immunosorbent assay. Multivariate linear regression analysis with enter method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In a separate study, the inflammatory response protein azurocidin (AZU1) was identified as being elevated in the serum of diabetic patients, especially in patients with diabetic complications including retinopathy [109]. This protein is released by neutrophils in response to inflammatory stimuli on vascular endothelium and is known to play a role in vascular permeability within the retina [110,111].…”
Section: Proteomic Changes In Biofluids Associated With Diabetic Rmentioning
confidence: 99%
“…In a separate study, the inflammatory response protein azurocidin (AZU1) was identified as being elevated in the serum of diabetic patients, especially in patients with diabetic complications including retinopathy [109]. This protein is released by neutrophils in response to inflammatory stimuli on vascular endothelium and is known to play a role in vascular permeability within the retina [110,111].…”
Section: Proteomic Changes In Biofluids Associated With Diabetic Rmentioning
confidence: 99%
“…Table (1) showed that there was no statistically significant difference between both groups regarding demographic data and risk factors (p > 0.05). Data are represented by mean ± SD.…”
Section: Resultsmentioning
confidence: 89%
“…Acute myocardial infarction (AMI) is one of the leading causes of morbidity and mortality throughout the world (1) . Acute transmural myocardial infarction induces ST-segment elevation, enlargement of the R wave, and widening of the QRS complex in electrocardiogram (ECG) leads, which are directly related to the ischemic region (2) .…”
Section: Introductionmentioning
confidence: 99%
“… 30 A clinical trial showed that the significant positive correlation of AZU1 with the SYNTAX score, Grace score and Killip class in MI patients, suggesting the strong association between inflammation and disease severity. 31 The mechanism remains unclear and demands further investigation. CAMP (also named as LL-37) is produced in the atherosclerotic lesions, where it may function as an immune modulator by activating adhesion molecule and chemokine expression, thus increasing innate immunity in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%